Divertor Development for a Future Fusion Power Plant - Norajitra, Prachai (KIT Scientific Publishing, 2011)
Nuclear fusion is considered as a future source of sustainable energy supply. Since the H-mode discovery in ASDEX experiment ""Divertor I"" in 1982, the divertor has been an integral part of all modern tokamaks and stellarators. The major goal of this thesis is to develop a feasible divertor design for a fusion power plant to be built after ITER. The thesis describes the approach in the conceptual development of a helium-cooled divertor and the methods of verification and validation of the design.
English
Keywords: machining and joining tungsten; Fusion power plant; high heat flux tests; helium impingement cooling; helium-cooled divertor